(untitled) (Bangladesh Journal of Medical Science, 2014)
Dental prostheses are very complex systems, heterogenous in structure, made up from various materials, with different physical properties. They have to satisfy high stress requirements as well as aesthetic challenges. The failures of dental prostheses lead to functional, aesthetic and phonetic disturbances which finally render the prosthetic treatment inefficient. OCT is a tomography imaging technology capable of producing high-resolution cross-sectional images of the internal architecture of materials and tissues. This includes not only the images of normal and abnormal dental hard tissue structures but also teeth after several treatment methods. It can be used for non-invasive investigations for both in-vivo and in-vitro structural imaging within the oral cavity. DOI: http://dx.doi.org/10.3329/bjms.v13i4.20553 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.388-390